Microgrid inverter control strategy based on augmented state feedback and dynamic feedforward compensation. (September 2022) - Li, Bingyu; Du, Xuhao; Fan, Hui; Liu, Zhen; Liu, Chao
Abstract: In order to improve the rapidity and immunity of microgrid inverter response, an inverter control structure with augmented state feedback plus dynamic feedforward is designed. The control structure is based on the augmented state feedback, robust mutual mass decomposition and Youla parameterisation theory, which can get the augmented state feedback control parameters and feedforward control structure, and the specific expression of feedforward controller is obtained by model matching theory, after which the Current loop compensation structure is added by combining the inverter and controller structures. The load switching and three-phase unbalance experiments are designed by Matlab/Simulink. The results show that without changing the structural parameters of the original system, the new controller can quickly stabilise the voltage fluctuation within 20 ms, change the fluctuation from 15 V to 2 V, and reduce the unbalance degree from 4% to less than 1%, effectively improving the response speed and anti-interference performance of the whole system, The speed and robustness of the inverter are improved.